2013
DOI: 10.3109/02688697.2013.798854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical efficacy of multiple lower-extremity nerve decompression in diabetic peripheral neuropathy

Abstract: Ultrasonography is capable of depicting these nerves morphological information, with respect to exact location, course, and extent. QST is suitable for early diagnosis of DPN, and abnormal QST is an indication of lower extremity nerve decompression for DPN. The joint use of QST and NCV testing helps surgeons to grasp the timing of surgery. High-resolution ultrasound, QST and NCV testing can also be used as an outcome index for surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
3
30
2
Order By: Relevance
“…Immediate pain relief in the recovery suite, bilateral pain improvement after unilateral surgery, and 80–92% of patients reporting relief were too astounding to believe, and no hypothesis for such an unexpected finding was proferred [17,2125]. Not dispositive.…”
Section: The Skeptics Casementioning
confidence: 99%
See 4 more Smart Citations
“…Immediate pain relief in the recovery suite, bilateral pain improvement after unilateral surgery, and 80–92% of patients reporting relief were too astounding to believe, and no hypothesis for such an unexpected finding was proferred [17,2125]. Not dispositive.…”
Section: The Skeptics Casementioning
confidence: 99%
“…Gondring et al [34] showed SWM monofilament evaluation of plantar sensation improved with tarsal tunnel ND, as did Mazilu et al [35]. Zhang et al [25] found post-op recovery of two-point sensibility to nearly normal levels. The level 1 EBM randomized control trial of Macare van Maurik et al [19] found lasting pain relief in operated limbs at 1 year, in comparison to the contralateral control limbs, which interestingly also improved and is pertinent to Cornblath et al’s [11] point 6.…”
Section: Subjective Outcomesmentioning
confidence: 99%
See 3 more Smart Citations